A synthesis method and application of intrinsic conductive epoxy resin
By using an intrinsic conductive epoxy resin synthesis method in photocured 3D printing materials, the conductive state is formed using π-electron conjugated structure and cyclic voltammetry experiments, the electrostatic accumulation problem caused by high insulation of the material is solved, and the excellent antistatic properties and part performance of 3D printed products are achieved.
Patent Information
- Application Number
- CN202411950249.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
AI Technical Summary
Due to its high insulation, existing photocured 3D printing materials are prone to electrostatic accumulation, electromagnetic wave interference and fire accidents, limiting their application in the field of antistatic.
By synthesis of intrinsic conductive epoxy resin, the conductive material with a π-electron conjugation structure was formed by copolymerization of 2,5-dimethoxy-1,3-terephthaldehyde and 3,5-diamino-1,2,4-triazole, and the P-type and N-type conductive states were formed through cyclic voltammetry experiments.
The stable conductivity of the material is achieved, which gives 3D printed products excellent anti-static properties, and maintains good light transmittance and part performance, solving the application limitations of existing conductive materials in 3D printing.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive materials, and in particular to a synthesis method and application of an intrinsic conductive epoxy resin. Background Art
[0002] In recent years, with the rapid development of 3D printing technology, 3D technology has been applied more and more widely in various industries, such as mold manufacturing, aerospace, medicine, machinery and other fields. Among them, light-curing 3D printing materials are polymer materials with high insulation properties. In actual application, static electricity accumulation, electromagnetic wave interference, damage to electronic components and other hazards will occur, and even cause the risk of major accidents such as fire and explosion, which seriously limits the application of light-curing 3D printing materials in the field of anti-static.
[0003] In order to eliminate the harm caused by static electricity, conventional antistatic treatment methods include: coating the surface of the material or mixing a certain amount of conductive filler or antistatic agent with lubrication and hygroscopicity inside the material, so that the highly insulating material has an antistatic effect. Common antistatic agents include: carbon materials (carbon black, carbon nanotubes, graphene), metal powders (silver powder, copper powder, etc.), metal oxides (tin oxide, copper oxide, zinc oxide, etc.) and some surface-active ionic and non-ionic antistatic agents.
[0004] At present, conventional antistatic methods are used to develop photocurable 3D printing materials, but there are fatal defects: First, carbon black has serious light absorption and poor UV transmittance, which seriously affects photocuring molding. A small amount of addition will not form a conductive network; Second, carbon nanotubes and graphene are also very black and have poor UV transmittance. At the same time, they are difficult to disperse, easy to agglomerate, and cannot be used in the medium and long term; Third, metal powders and metal oxide powders are very easy to settle in 3D printing materials and cannot be used in the medium and long term; Fourth, the addition of ionic and non-ionic antistatic agents with surface activity is large, which can easily cause a decrease in material strength and toughness. The antistatic effect of this method will also weaken over time, and it is a non-permanent antistatic agent.
[0005] Therefore, it is necessary to propose a synthesis method of an intrinsic conductive epoxy resin to overcome the defects of conductive materials in the prior art and to meet the antistatic properties of photocurable 3D printing materials. Summary of the invention
[0006] The present invention provides a method for synthesizing an intrinsic conductive epoxy resin, which overcomes the defects of conductive materials in the prior art and satisfies the antistatic properties of light-cured 3D printing materials.
[0007] In view of this, the scheme of the present invention is:
[0008] The first aspect of the present invention is to provide an intrinsic conductive epoxy resin having a structural formula shown in Formula I:
[0009]
[0010] The second aspect of the present invention is to provide a method for synthesizing the intrinsic conductive epoxy resin described in the first aspect, the steps comprising:
[0011] S1. 2,5-dimethoxy-1,3-terephthalaldehyde and 3,5-diamino-1,2,4-triazole are placed in solvent 1, stirred and refluxed under inert gas for 18 to 24 hours, and the product is filtered and dried to obtain intermediate 1;
[0012] S2. Intermediate 1 undergoes a reduction reaction with hydrogen in the presence of catalyst 1 to obtain intermediate 2;
[0013] S3. Intermediate 2 undergoes a substitution reaction with epichlorohydrin in the presence of catalyst 2 to obtain intermediate 3;
[0014] S4. The intermediate three was placed in proton acid as a working electrode for cyclic voltammetry experiments, the working electrode was removed, and the product was scraped off after drying to obtain an intrinsic conductive epoxy resin with a structure shown in Formula I;
[0015] The synthesis method reaction route is as follows:
[0016]
[0017] Further, in step S1:
[0018] The mass ratio of the 2,5-dimethoxy-1,3-terephthalaldehyde to 3,5-diamino-1,2,4-triazole is (2-4):1;
[0019] and / or, the first solvent is an alcohol solvent selected from ethanol, methanol, isopropanol, and 2-butanol;
[0020] And / or, the reflux reaction temperature is 60-110°C.
[0021] Further, in step S2:
[0022] The catalyst 1 is selected from at least one of palladium carbon and platinum carbon, and the amount used is 1 to 5 times the mass of the intermediate 1;
[0023] And / or, the solvent used in the reaction process is an aromatic hydrocarbon solvent;
[0024] And / or, the reduction reaction condition is stirring at a temperature of 100 to 120° C. for 6 to 8 hours.
[0025] Further, in step S3, the substitution reaction process is carried out in an inert atmosphere;
[0026] And / or, the second catalyst is selected from tetrabutylammonium bromide, hexadecyltrimethylammonium bromide or benzyltriethylammonium chloride; the amount of the second catalyst is 3 to 6 times the mass of the second intermediate.
[0027] Furthermore, in step S3, the reaction process is first heated to 80-100° C., stirred for 8-10 h, and then alkaline solution is added dropwise and stirred at 60° C. for 6-8 h.
[0028] Further, in step S4:
[0029] The protonic acid is selected from one of sulfuric acid, sulfosalicylic acid, citric acid or p-toluenesulfonic acid;
[0030] And / or, the cyclic voltammetry experiment conditions are: potential window 0-0.7V, scan rate 50mV / s, and 50 cycles.
[0031] The third aspect of the present invention is to propose the use of the intrinsic conductive epoxy resin described in the first aspect or the intrinsic conductive epoxy resin obtained by the preparation method described in the second aspect in photocuring 3D printing.
[0032] The fourth aspect of the present invention is to provide a photosensitive resin composition, which comprises the following components in parts by weight:
[0033] 10-40 parts of conductive epoxy resin, 20-40 parts of alicyclic epoxy resin, 5-10 parts of glycidyl ether monomer, 10-20 parts of oxygen heterocyclic monomer, 2-5 parts of initiator, and 0.05-1 part of pigment; the conductive epoxy resin is the intrinsic conductive epoxy resin described in the first aspect or the intrinsic conductive epoxy resin obtained by the preparation method described in the second aspect.
[0034] A fifth aspect of the present invention is to provide a 3D printed product, which is obtained by 3D printing and curing the photosensitive resin composition described in the fourth aspect.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The main structure of the intrinsic conductive epoxy resin of the present invention is obtained by copolymerization of 2,5-dimethoxy-1,3-terephthalaldehyde and 3,5-diamino-1,2,4-triazole. The electrical activity originates from the π electron conjugated structure in the molecular chain: as the π electron system in the molecular chain expands, the π bonding state and the π* anti-bonding state form the valence band and the conduction band respectively. This non-localized π electron conjugated structure forms P-type and N-type conductive states after doping. During the doping process, H +The nitrogen atom on the imine is protonated, and this protonation causes holes to appear on the valence band of the doped segment on the main chain, that is, P-type doping, forming a stable delocalized imine atom group. The positive charge carried by the imine nitrogen atom is dispersed to the adjacent atoms along the molecular chain through conjugation, thereby increasing the stability of the system. Under the action of an external electric field, the resonance of conjugated π electrons causes the holes to move on the entire chain segment, so that the polymer exhibits higher conductivity.
[0037] The intrinsic conductive epoxy resin proposed in the present invention solves the limitation problem of the application of existing conventional conductive materials in 3D printing materials, and is applied to epoxy resin-based liquid photosensitive resin for SLA printing, participates in photopolymerization reaction, forms a three-dimensional interpenetrating network structure, and gives the printed products excellent antistatic properties, and gives the products good light transmittance, excellent product performance and stability. DETAILED DESCRIPTION
[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the preferred embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] In one embodiment, an intrinsic conductive epoxy resin is provided, having a structural formula shown in Formula I:
[0040]
[0041] The intrinsic conductive epoxy resin can be used as a cationic photocurable resin component and is suitable for SLA printing liquid photosensitive resin. The molecular chain contains a π electron conjugated structure: as the π electron system in the molecular chain expands, the π bonding state and the π* antibonding state form a valence band and a conduction band respectively, and this non-localized π electron conjugated structure forms a P-type and N-type conductive state after doping, giving the SLA printing liquid photosensitive resin an antistatic function.
[0042] In another embodiment, a method for preparing an intrinsic conductive epoxy resin having a structure shown in the above formula I is provided, and the steps are as follows:
[0043] 1. Take 2-4g 2,5-dimethoxy-1,3-terephthalaldehyde and 1g 3,5-diamino-1,2,4-triazole and dissolve them in 100mL alcohol solvent, add them into a 250ml three-necked flask equipped with a reflux condenser. Stir at room temperature until completely dissolved, then gradually heat to 60-110°C and stir under a nitrogen atmosphere for 18-24h. The obtained precipitate is filtered and washed three times with anhydrous ethanol to remove impurities. Then dry in an oven at 60°C for 12 hours to obtain intermediate 1;
[0044] 2. Take 1g of dried intermediate 1 and dissolve it in 100mL of aromatic hydrocarbon solvent, add it to a 250ml three-necked flask, add 1-5g of catalyst A, pass H2, 100-120℃, stir for 6-8h, filter the solution, and rotary evaporate the filtrate to obtain intermediate 2;
[0045] The reaction routes of the preparation of intermediate 1 and intermediate 2 in steps 1 to 2 are as follows:
[0046]
[0047] 3. Take 1g of intermediate 2, 300-600mL of epichlorohydrin and 3-6g of catalyst B and add them into a 1000mL three-necked flask. Heat to 80-100℃ under N2 protection and stir for 8-10h. Cool the reaction mixture to room temperature and wash with deionized water, separate the phases and evaporate them to obtain intermediate 3.
[0048] 4. Take 1g of the electrode material produced in step 3 and conduct a cyclic voltammetry experiment in 300-500mL 1mol / L protonic acid. After the experiment, take out the working electrode from the electrolyte and dry it, scrape off the product, and obtain the intrinsic conductive epoxy resin.
[0049] Steps 3 to 4 are as follows for preparing intermediate III and the final product:
[0050]
[0051] In a preferred embodiment, the catalyst A is one of palladium carbon and platinum carbon; the catalyst B is selected from tetrabutylammonium bromide, hexadecyltrimethylammonium bromide or benzyltriethylammonium chloride.
[0052] In a preferred embodiment, the alcohol solvent is selected from at least one of ethanol, methanol, isopropanol, and 2-butanol. Those skilled in the art can select a suitable alcohol or a combination thereof according to the reflux temperature; the aromatic hydrocarbon solvent is selected from one or more of benzene, toluene, and xylene.
[0053] In a preferred embodiment, during the preparation of intermediate three from epichlorohydrin, the mixture is heated to 80-100° C. and stirred for 8-10 hours. Then, in order to neutralize the acid produced during the reaction and facilitate the continued forward reaction and the completion of the reaction, 200 mL of a 20 wt % NaOH aqueous solution is added dropwise to the mixture and stirred at 60° C. for 6-8 hours.
[0054] In a preferred embodiment, the protonic acid is sulfuric acid, sulfosalicylic acid, citric acid or p-toluenesulfonic acid.
[0055] In a preferred embodiment, the cyclic voltammetry experiment conditions are: potential window 0-0.7V, scan rate 50mV / s, and 50 cycles. The cyclic voltammetry experiment can ionize the imino group in the triazole ring to achieve H + Doping. The conductive effect of the doped polymer is greatly improved.
[0056] In another embodiment, a liquid photosensitive resin for SLA printing is provided, which is an epoxy resin-based liquid photosensitive resin and includes the following components in parts by weight:
[0057] 10-40 parts of intrinsic conductive epoxy resin of formula I
[0058] Alicyclic epoxy resin 20-40 parts
[0059] 5-10 parts of glycidyl ether monomer
[0060] 10-20 parts of oxygen heterocyclic monomer
[0061] Initiator 2-5 parts
[0062] Pigment 0.05-1 part.
[0063] In the above embodiment, the intrinsic conductive epoxy resin of Formula I is applied to the epoxy resin-based liquid photosensitive resin for SLA printing, participates in the photopolymerization reaction, forms a three-dimensional interpenetrating network structure, and gives the printed product excellent antistatic properties, and gives the product good light transmittance, excellent product performance and stability.
[0064] In a preferred embodiment, the epoxy resin is one or a mixture of two or more of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester, bis((3,4-epoxycyclohexyl)methyl)adipate, and 3,4-epoxycyclohexyl methacrylate.
[0065] In a preferred embodiment, the glycidyl ether monomer is one or a mixture of two or more of allyl glycidyl ether, benzyl glycidyl ether, polyethylene glycol diglycidyl ether, C12-14 alkyl glycidyl ether, and glycerol triglycidyl ether.
[0066] In a preferred embodiment, the heterocyclic monomer is one or a mixture of two or more of oxetan-4-ol, 2-(tetrahydrofuran-2-yl)ethanol, tetrahydrofuranmethanol, and 2-(oxetane-2-yl)ethanol.
[0067] In a preferred embodiment, the initiator is one or a mixture of two or more of diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate, triphenylsulfonium phosphine hexafluoride, triarylsulfonium hexafluorophosphate, and diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate.
[0068] In a preferred embodiment, the pigment is titanium dioxide, carbon black, benzidine yellow, permanent orange or permanent orange, and those skilled in the art can select the pigment according to their needs.
[0069] The following are preferred implementation examples. If the manufacturer of the reagent or instrument is not specified in the examples, conventional products can be purchased from the market. If the specific conditions are not specified, conventional conditions or conditions recommended by the manufacturer can be used.
[0070] Example 1
[0071] 1. Take 2g of 2,5-dimethoxy-1,3-terephthalaldehyde and 1g of 3,5-diamino-1,2,4-triazole and dissolve them in ethanol (100mL), add them to a 250mL three-necked flask equipped with a reflux condenser. Stir at room temperature until completely dissolved, then gradually heat to 70°C and stir for 24h under a nitrogen atmosphere. The resulting precipitate is filtered and washed three times with anhydrous ethanol to remove impurities. Then dry in an oven at 60°C for 12 hours to obtain the intermediate product;
[0072] 2. Take 1g of the dried product of step 1 and dissolve it in 100mL of benzene, add it to a 250ml three-necked flask, add 5g of palladium carbon, pass H2, 100°C, stir for 6h, filter the solution, and rotary evaporate to obtain an intermediate product;
[0073] 3. Take 1g of the intermediate product of step 2, 300mL of epichlorohydrin and 3g of tetrabutylammonium bromide and add them into a 1000mL three-necked flask. Heat to 90°C under N2 protection and stir for 8h. Then drop 200mL of 20wt% NaOH aqueous solution into the mixture and stir at 60°C for 6h. Cool the reaction mixture to room temperature and wash with deionized water to remove impurities. Rotary evaporate to obtain the final product.
[0074] 4. Take 1g of the electrode material produced in step 3 and conduct a cyclic voltammetry experiment in 300mL 1mol / L sulfuric acid, with a potential window of 0-0.7V, a scan rate of 50mV / s, and 50 cycles. After the experiment, take the working electrode out of the electrolyte and dry it, scrape off the product, and obtain an intrinsic conductive epoxy resin.
[0075] 40 parts of intrinsic conductive epoxy resin, 20 parts of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester, 5 parts of allyl glycidyl ether, 10 parts of oxacycloheptan-4-ol, 2 parts of diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate and 0.05 parts of permanent orange were mixed and stirred for 30 minutes to obtain an epoxy resin-based liquid photosensitive resin.
[0076] Example 2
[0077] 1. Take 2.5g of 2,5-dimethoxy-1,3-terephthalaldehyde and 1g of 3,5-diamino-1,2,4-triazole and dissolve them in methanol (100mL), add them to a 250mL three-necked flask equipped with a reflux condenser. Stir at room temperature until completely dissolved, then gradually heat to 60°C and stir for 18h under a nitrogen atmosphere. The resulting precipitate is filtered and washed three times with anhydrous ethanol to remove impurities. Then dry in an oven at 60°C for 12 hours to obtain the intermediate product;
[0078] 2. Take 1g of the dried product of step 1 and dissolve it in 100mL of benzene, add it to a 250ml three-necked flask, add 2g of palladium carbon, pass H2, 110°C, stir for 6h, filter the solution, and rotary evaporate to obtain an intermediate product;
[0079] 3. Take 1g of the intermediate product of step 2, 400mL of epichlorohydrin and 3.5g of tetrabutylammonium bromide and add them into a 1000mL three-necked flask. Heat to 80°C under N2 protection and stir for 8h. Then drop 200mL of 20wt% NaOH aqueous solution into the mixture and stir at 60°C for 7h. Cool the reaction mixture to room temperature and wash with deionized water to remove impurities. Rotary evaporate to obtain the final product.
[0080] 4. Take 1g of the electrode material produced in step 3 and conduct a cyclic voltammetry experiment in 500mL of 1mol / L sulfosalicylic acid, with a potential window of 0-0.7V, a scan rate of 50mV / s, and 50 cycles. After the experiment, take the working electrode out of the electrolyte and dry it, scrape off the product, and obtain an intrinsic conductive epoxy resin.
[0081] 30 parts of intrinsic conductive epoxy resin, 30 parts of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester, 8 parts of benzyl glycidyl ether, 20 parts of 2-(tetrahydrofuran-2-yl)ethanol, 3 parts of triphenylsulfonium hexafluoride phosphonium salt and 0.5 parts of benzidine yellow were mixed and stirred for 30 minutes to obtain an epoxy resin-based liquid photosensitive resin.
[0082] Example 3
[0083] 1. Take 3g of 2,5-dimethoxy-1,3-terephthalaldehyde and 1g of 3,5-diamino-1,2,4-triazole and dissolve them in isobutyl alcohol (100mL), add them into a 250mL three-necked flask equipped with a reflux condenser. Stir at room temperature until completely dissolved, then gradually heat to 85°C and stir for 20h under a nitrogen atmosphere. The resulting precipitate is filtered and washed three times with anhydrous ethanol to remove impurities. Then dry in an oven at 60°C for 12 hours to obtain the intermediate product;
[0084] 2. Take 1g of the dried product of step 1 and dissolve it in 100mL of toluene, add it to a 250ml three-necked flask, add 1g of platinum carbon, pass H2, 120°C, stir for 8h, filter the solution, and rotary evaporate to obtain an intermediate product;
[0085] 3. Take 1g of the intermediate product of step 2, 500mL of epichlorohydrin and 4g of hexadecyltrimethylammonium bromide and add them into a 1000mL three-necked flask. Heat to 100°C under N2 protection and stir for 10h. Then drop 200mL of 20wt% NaOH aqueous solution into the mixture and stir at 60°C for 8h. Cool the reaction mixture to room temperature and wash with deionized water to remove impurities. Rotary evaporate to obtain the final product.
[0086] 4. Take 1g of the electrode material produced in step 3 and conduct a cyclic voltammetry experiment in 400mL 1mol / L citric acid, with a potential window of 0-0.7V, a scan rate of 50mV / s, and 50 cycles. After the experiment, take the working electrode out of the electrolyte and dry it, scrape off the product, and obtain an intrinsic conductive epoxy resin.
[0087] 20 parts of intrinsic conductive epoxy resin, 40 parts of bis((3,4-epoxycyclohexyl)methyl) adipate, 10 parts of polyethylene glycol diglycidyl ether, 20 parts of tetrahydrofuran methanol, 5 parts of triaryl sulfonium hexafluorophosphate and 1 part of titanium dioxide were mixed and stirred for 30 minutes, and poured into the resin tank of a 3D printer to obtain an epoxy resin-based liquid photosensitive resin.
[0088] Example 4
[0089] 1. Take 3.5g of 2,5-dimethoxy-1,3-terephthalaldehyde and 1g of 3,5-diamino-1,2,4-triazole and dissolve them in isobutyl alcohol (100mL), add them into a 250mL three-necked flask equipped with a reflux condenser. Stir at room temperature until completely dissolved, then gradually heat to 90°C and stir for 22h under a nitrogen atmosphere. The resulting precipitate is filtered and washed three times with anhydrous ethanol to remove impurities. Then dry in an oven at 60°C for 12 hours to obtain the intermediate product;
[0090] 2. Take 1g of the dried product of step 1 and dissolve it in 100mL of toluene, add it to a 250ml three-necked flask, add 2g of platinum carbon, pass H2, 100°C, stir for 6h, filter the solution, and rotary evaporate to obtain an intermediate product;
[0091] 3. Take 1g of the intermediate product of step 2, 600mL of epichlorohydrin and 6g of hexadecyltrimethylammonium bromide and add them into a 1000mL three-necked flask. Heat to 90°C under N2 protection and stir for 10h. Then drop 200mL of 20wt% NaOH aqueous solution into the mixture and stir at 60°C for 8h. Cool the reaction mixture to room temperature and wash with deionized water to remove impurities. Rotary evaporate to obtain the final product.
[0092] 4. Take 1g of the electrode material produced in step 3 and conduct a cyclic voltammetry experiment in 350mL 1mol / L p-toluenesulfonic acid, with a potential window of 0-0.7V, a scan rate of 50mV / s, and 50 cycles. After the experiment, take the working electrode out of the electrolyte and dry it, scrape off the product, and obtain an intrinsic conductive epoxy resin.
[0093] 10 parts of intrinsic conductive epoxy resin, 40 parts of bis((3,4-epoxycyclohexyl)methyl)adipate, 10 parts of C12-14 alkyl glycidyl ether, 15 parts of 2-(oxetane-2-yl)ethanol, 4 parts of diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate and 0.2 parts of carbon black were mixed and stirred for 30 minutes to obtain an epoxy resin-based liquid photosensitive resin.
[0094] Example 5
[0095] 1. Take 3.5g of 2,5-dimethoxy-1,3-terephthalaldehyde and 1g of 3,5-diamino-1,2,4-triazole and dissolve them in 2-butanol (100mL), add them to a 250mL three-necked flask equipped with a reflux condenser. Stir at room temperature until completely dissolved, then gradually heat to 100°C and stir for 24h under a nitrogen atmosphere. The resulting precipitate is filtered and washed three times with anhydrous ethanol to remove impurities. Then dry in an oven at 60°C for 12 hours to obtain the intermediate product;
[0096] 2. Take 1g of the dried product of step 1 and dissolve it in 100mL of xylene, add it to a 250ml three-necked flask, add 3g of platinum carbon, pass H2, 120°C, stir for 8h, filter the solution, and rotary evaporate to obtain an intermediate product;
[0097] 3. Take 1g of the intermediate product of step 2, 600mL of epichlorohydrin and 6g of benzyltriethylammonium chloride and add them into a 1000mL three-necked flask. Heat to 100°C under N2 protection and stir for 6h. Then drop 200mL of 20wt% NaOH aqueous solution into the mixture and stir at 60°C for 6h. Cool the reaction mixture to room temperature and wash with deionized water to remove impurities. Rotary evaporate to obtain the final product.
[0098] 4. Take 1g of the electrode material produced in step 3 and conduct a cyclic voltammetry experiment in 450mL of 1mol / L citric acid, with a potential window of 0-0.7V, a scan rate of 50mV / s, and 50 cycles. After the experiment, take the working electrode out of the electrolyte and dry it, scrape off the product, and obtain an intrinsic conductive epoxy resin.
[0099] 30 parts of intrinsic conductive epoxy resin, 40 parts of 3,4-epoxycyclohexyl methacrylate, 6 parts of propylene glycol triglycidyl ether, 12 parts of 2-(oxetane-2-yl)ethanol, 4 parts of diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate and 0.6 parts of permanent orange were mixed and stirred for 30 minutes to obtain an epoxy resin-based liquid photosensitive resin.
[0100] Example 6
[0101] 1. Take 2.8g of 2,5-dimethoxy-1,3-terephthalaldehyde and 1g of 3,5-diamino-1,2,4-triazole and dissolve them in 2-butanol (100mL), add them to a 250mL three-necked flask equipped with a reflux condenser. Stir at room temperature until completely dissolved, then gradually heat to 110°C and stir for 24h under a nitrogen atmosphere. The resulting precipitate is filtered and washed three times with anhydrous ethanol to remove impurities. Then dry in an oven at 60°C for 12 hours to obtain the intermediate product;
[0102] 2. Take 1g of the dried product of step 1 and dissolve it in 100mL of xylene, add it to a 250ml three-necked flask, add 4g of platinum carbon, pass H2, 120°C, stir for 6h, filter the solution, and rotary evaporate to obtain an intermediate product;
[0103] 3. Take 1g of the intermediate product of step 2, 550mL of epichlorohydrin and 5.5g of catalyst B and add them into a 1000mL three-necked flask. Heat to 80°C under N2 protection and stir for 10h. Then drop 200mL of 20wt% NaOH aqueous solution into the mixture and stir at 60°C for 8h. Cool the reaction mixture to room temperature and wash with deionized water to remove impurities. Rotary evaporate to obtain the final product.
[0104] 4. Take 1g of the electrode material produced in step 3 and conduct a cyclic voltammetry experiment in 400mL 1mol / L p-toluenesulfonic acid, with a potential window of 0-0.7V, a scan rate of 50mV / s, and 50 cycles. After the experiment, take the working electrode out of the electrolyte and dry it, scrape off the product, and obtain an intrinsic conductive epoxy resin.
[0105] 40 parts of intrinsic conductive epoxy resin, 40 parts of 3,4-epoxycyclohexyl methacrylate, 8 parts of benzyl glycidyl ether, 15 parts of 2-(tetrahydrofuran-2-yl)ethanol, 5 parts of triphenylsulfonium phosphine hexafluoride and 0.1 parts of carbon black were mixed and stirred for 30 minutes, and poured into the resin tank of a 3D printer to obtain an epoxy resin-based liquid photosensitive resin.
[0106] Comparative Example 1
[0107] 40 parts of bis((3,4-epoxycyclohexyl)methyl)adipate, 10 parts of C12-14 alkyl glycidyl ether, 15 parts of 2-(oxetane-2-yl)ethanol, 4 parts of diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate and 10 parts of conductive carbon black (VXC-72; Cabot) were mixed and stirred for 30 minutes to obtain an epoxy resin-based liquid photosensitive resin.
[0108] Comparative Example 2
[0109] 40 parts of bis((3,4-epoxycyclohexyl)methyl)adipate, 10 parts of C12-14 alkyl glycidyl ether, 15 parts of 2-(oxetane-2-yl)ethanol, 4 parts of diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate and 1 part of multi-walled carbon nanotubes (Shanghai Gangtian) were mixed and stirred for 30 minutes to obtain an epoxy resin-based liquid photosensitive resin.
[0110] Comparative Example 3
[0111] 40 parts of bis((3,4-epoxycyclohexyl)methyl)adipate, 10 parts of C12-14 alkyl glycidyl ether, 15 parts of 2-(oxetane-2-yl)ethanol, 4 parts of diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate and 10 parts of zinc oxide powder were mixed and stirred for 30 minutes to obtain an epoxy resin-based liquid photosensitive resin.
[0112] Comparative Example 4
[0113] 40 parts of bis((3,4-epoxycyclohexyl)methyl)adipate, 10 parts of C12-14 alkyl glycidyl ether, 15 parts of 2-(oxetane-2-yl)ethanol, 4 parts of diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate and 10 parts of an ionic conductive agent (TM124; Shandong Juli) were mixed and stirred for 30 minutes to obtain an epoxy resin-based liquid photosensitive resin.
[0114] Comparative Example 5
[0115] 40 parts of bis((3,4-epoxycyclohexyl)methyl)adipate, 10 parts of C12-14 alkyl glycidyl ether, 15 parts of 2-(oxetane-2-yl)ethanol, 4 parts of diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate and 10 parts of polyvinylpyrrolidone (non-ionic conductive agent) were mixed and stirred for 30 minutes to obtain an epoxy resin-based liquid photosensitive resin.
[0116] Test Case
[0117] The epoxy resin-based liquid photosensitive resins prepared in the above Examples 1 to 6 and Comparative Examples 1 to 5 were respectively poured into the resin tank of a 3D printer, and parts were respectively produced by SLA 3D printing to obtain 3D printed three-dimensional objects. The SLA equipment used was: Liantai-Lite-100, and the equipment molding light source was 355nm.
[0118] The surface resistivity and volume resistivity of the samples were tested according to GB / T 1410-2006 “Test method for volume resistivity and surface resistivity of solid insulating materials”.
[0119] The antistatic photocurable materials prepared in Examples 1 to 6 and Comparative Examples 1 to 5 were used to perform SLA 3D printing test samples, and the conductive properties and product properties of the test samples were tested. The specific results are shown in Tables 1 and 2.
[0120] Table 1:
[0121] Example Surface resistivity(Ω) Volume resistivity (Ω*m) Example 1 <![CDATA[10 7 ]]> <![CDATA[10 7 ]]> Example 2 <![CDATA[10 7 ]]> <![CDATA[10 7 ]]> Example 3 <![CDATA[10 9 ]]> <![CDATA[10 9 ]]> Example 4 <![CDATA[10 9 ]]> <![CDATA[10 9 ]]> Example 5 <![CDATA[10 7 ]]> <![CDATA[10 7 ]]> Example 6 <![CDATA[10 7 ]]> <![CDATA[10 7 ]]> Comparative Example 1 <![CDATA[10 11 ]]> <![CDATA[10 11 ]]> Comparative Example 2 <![CDATA[10 11 ]]> <![CDATA[10 11 ]]> Comparative Example 3 <![CDATA[10 10 ]]> <![CDATA[10 10 ]]> Comparative Example 4 <![CDATA[10 10 ]]> <![CDATA[10 10 ]]> Comparative Example 5 <![CDATA[10 11 ]]> <![CDATA[10 11 ]]>
[0122] Table 2:
[0123]
[0124] It is not difficult to see from Table 1 that the epoxy resin-based liquid photosensitive resin prepared in Examples 1 to 6 has excellent conductive properties after being made into parts by 3D printing due to the addition of intrinsic conductive epoxy resin. In addition, Table 2 can clearly show that the parts of Example 4 have excellent performance in terms of ultraviolet transmittance and part performance, and the intrinsic conductive epoxy resin has good dispersion stability in the epoxy resin-based liquid photosensitive resin, and the storage stability of the parts is excellent. Compared with the ordinary type of conductive agent, the performance is significantly improved, indicating that the intrinsic conductive epoxy resin is applied to the epoxy resin-based liquid photosensitive resin for SLA printing, participates in the photopolymerization reaction, and forms a three-dimensional interpenetrating network structure, which gives the printed product excellent antistatic properties, and gives the parts good light transmittance, excellent part performance and stability.
[0125] The epoxy resin-based liquid photosensitive resin prepared in Examples 1 to 6 was subjected to SLA 3D printing test samples to perform performance tests in terms of strength and toughness. The results are shown in Table 3.
[0126] Table 3:
[0127]
[0128] Note: Elongation at break and impact strength are usually used to indicate the toughness of a material.
[0129] The data in Table 3 show that the products printed with epoxy resin-based liquid photosensitive resin added with intrinsic conductive epoxy resin have good strength and toughness, and can reach the level of industrial material use.
[0130] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. Intrinsic conductive epoxy resin, characterized in that: It has the structural formula shown in Formula I: 。 2. The method for synthesizing the intrinsic conductive epoxy resin according to claim 1, characterized in that the steps include: S1. 2,5-dimethoxy-1,3-terephthalaldehyde and 3,5-diamino-1,2,4-triazole are placed in solvent 1, stirred and refluxed under inert gas for 18 to 24 hours, and the product is filtered and dried to obtain intermediate 1; S2. Intermediate 1 undergoes a reduction reaction with hydrogen in the presence of catalyst 1 to obtain intermediate 2; S3. Intermediate 2 undergoes a substitution reaction with epichlorohydrin in the presence of catalyst 2 to obtain intermediate 3; S4. The intermediate three was placed in proton acid as a working electrode for cyclic voltammetry experiments, the working electrode was removed, and the product was scraped off after drying to obtain an intrinsic conductive epoxy resin with a structure shown in Formula I; The synthesis method reaction route is as follows:
3. The synthesis method according to claim 2, characterized in that In step S1: The mass ratio of the 2,5-dimethoxy-1,3-terephthalaldehyde to 3,5-diamino-1,2,4-triazole is (2-4):1; and / or, the first solvent is an alcohol solvent selected from ethanol, methanol, isopropanol, and 2-butanol; And / or, the reflux reaction temperature is 60-110°C.
4. The synthesis method according to claim 2, characterized in that In step S2: The catalyst 1 is selected from at least one of palladium carbon and platinum carbon; And / or, the solvent used in the reaction process is an aromatic hydrocarbon solvent; And / or, the reduction reaction condition is stirring at a temperature of 100 to 120° C. for 6 to 8 hours.
5. The synthesis method according to claim 2, characterized in that In step S3, the substitution reaction process is carried out in an inert atmosphere; And / or, the second catalyst is selected from tetrabutylammonium bromide, hexadecyltrimethylammonium bromide or benzyltriethylammonium chloride.
6. The synthesis method according to claim 2, characterized in that In step S3, the reaction process is first heated to 80-100° C., stirred for 8-10 hours, then alkaline solution is added dropwise, and stirred at 60° C. for 6-8 hours.
7. The synthesis method according to claim 2, characterized in that In step S4: The protonic acid is selected from one of sulfuric acid, sulfosalicylic acid, citric acid or p-toluenesulfonic acid; And / or, the cyclic voltammetry experiment conditions are: potential window 0-0.7V, scan rate 50mV / s, and 50 cycles.
8. Use of the intrinsic conductive epoxy resin according to claim 1 or the intrinsic conductive epoxy resin obtained by the preparation method according to any one of claims 2 to 7 in photocuring 3D printing.
9. A photosensitive resin composition, characterized in that: In parts by weight, it includes the following components: 10-40 parts of conductive epoxy resin, 20-40 parts of alicyclic epoxy resin, 5-10 parts of glycidyl ether monomer, 10-20 parts of oxygen heterocyclic monomer, 2-5 parts of initiator, 0.05-1 part of pigment; the conductive epoxy resin is the intrinsic conductive epoxy resin according to claim 1 or the intrinsic conductive epoxy resin obtained by the preparation method according to any one of claims 2-7.
10. A 3D printed product, characterized in that: The photosensitive resin composition according to claim 9 is 3D printed and cured.
Citation Information
Cited By
Preparation method of hyperbranched intrinsic conductive epoxy resin, resin composition containing hyperbranched intrinsic conductive epoxy resin and application of hyperbranched intrinsic conductive epoxy resin
CN121652374A